Understanding Poverty and Inequality in Egypt : Background Papers - World Bank Group (World Bank, Washington, DC, 2019)
The previous decade in Egypt was marked by major internal and external shocks that have surely had severe implications for the evolution of the population’s welfare. In recent years, social, political, and economic changes have transformed the landscape of the Egyptian society. On January 2011, the revolution started. Led by wide protests and social discontent, the movement ended with the ousting then president. His toppling was followed by two presidential elections in two years. Given the structural constraints to macroeconomic stability and fiscal pressures, the government engaged in a series of economic reforms to reel in spending and set the country in a sustainable path. It is critical to understand how the welfare of Egyptian households evolved during this period. Analyzing who were affected the most is key to assessing what the future conditions hold for their welfare and how policies can be better designed to protect them. The objectives of this paper are twofold. The first is to provide a detailed description of the methodology that has been applied in Egypt in estimating poverty, including the decisions taken to build the consumption-based welfare aggregate. The second objective of this note is to understand how the events from recent years have affected households’ living conditions.